Characterization of grain boundaries in CdTe polycrystalline films - Tetyorkin, V.V.; Sukach, A.V.; Boiko, V.A.; Tkachuk, A.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
CdTe polycrystalline films with the average size of grains within the range 10…360 μm were grown on sapphire substrates by using the modified close-spaced sublimation technique. Transverse (across the film) and lateral (along the film’s surface) conductivity as a function of bias voltage and temperature were measured using appropriate arrangement of contacts. The transverse conductivity exhibits ohmic behavior, whereas the lateral transport of carriers is dominated by potential barriers at the grain boundaries. The carrier concentration in the grains and the potential barrier height have been estimated. The inhomogeneous distribution of deep defects through the grains was found from the photoluminescence measurements.